High energy efficient analog compressed sensing encoder for wireless ECG system. (October 2016) - Wang, Yishan; Doleschel, Sammy; Wunderlich, Ralf; Heinen, Stefan
Abstract: This paper proposed a high energy efficient analog compressed sensing encoder for wireless ECG system, where the input analog signal is multiplied by the random matrix and the products are integrated on the Multiplying Digital-to-Analog Converter/Integrators (MDAC/Is). Only one ADC is applied in this paper to sample 64 channels of MDAC/Is, compared with 64 channels of ADC in other design. Finally, the digitized measurement vector is obtained. The encoder was designed and simulated in a 0.13 μm CMOS process. Current leakages of the switches in MDAC/Is are cautiously considered. Several leakage suppression structures are employed. The leakage current in every switch is reduced to several fA. The average power consumption of the whole encoder is 23.5 μW. Signal-to-noise ratios (SNRs) of the reconstructed signal are 48.3 dB and 28.1 dB for Compressed Ratio (CR)=2 and 4 respectively.